The Role of Illustration in Self-Protection Education: A Study in Books "Saat Tiara dalam Bahaya" for Parents and Children with Special Needs - Siregar, Pungki; Mutmainah, Siti (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2026)
This study aims to examine the role of illustration in the book When Tiara is in Danger (Saat Tiara dalam Bahaya): Teach Children to Protect Themselves from Sexual Violence with NO! GO! TELL! through visual and narrative semiotic approaches. This research uses a descriptive qualitative method. The research objects include visual elements of the book, such as illustrations, colors, character expressions, visual symbols, and supporting elements in the form of icons and disability language symbols. Data collection was carried out through documentation studies and systematic visual observation of all pages of the book. Data analysis was carried out using semiotics theory, including signifier-signified relationships, types of signs (icons, indexes, symbols), and visual grammar which includes representational, interactional, and compositional meanings. The results of the study show that illustrations play a role in building empathy, providing warnings, and strengthening self-protection actions. The use of bright colors, explicit visual expressions, consistent symbols, and the repetition of signs help children understand abstract concepts such as dangers and body boundaries more easily. In addition, the presence of disability language symbols strengthens the accessibility of messages and supports an inclusive approach to self-protection education.